Kharita: the royal art of letter dispatching. Issue 1 (April 2019) - Zeir, Ula
Abstract : The practice of dispatching kharita had been part of the royal correspondence of Muslim rulers for centuries, particularly in Persia and India. Originating from Arabic, the term kharita refers to a pouch fabricated from leather or silk, or possibly other material. Although the dictionary definition applies to the pouch itself, the act of sending a kharita indicates that a royal letter is placed inside the pouch. Therefore, a kharita is the pouch and its contents. The article examines one particular kharita (Mss Eur F111/361, ff 2–5 at the British Library). The study identifies the elements that comprise the kharita item, and make it a piece of royal art.